Redescription of Biacetabulum giganteum Hunter, 1929 (Cestoda: Caryophyllidea), description of two new, closely related species from suckers (Catostomidae) in North America, and a critical review of host specificity of species of Biacetabulum Hunter, 1927. Issue 8 (17th November 2021) - Uhrovič, Dalibor; Oros, Mikuláš; Reyda, Florian; Kudlai, Olena; Scholz, Tomáš
Abstract : Morphological and molecular evaluation of tapeworms of the order Caryophyllidea from suckers (Cypriniformes: Catostomidae) in North America made it possible to redescribe the insufficiently known and rare species Biacetabulum giganteum Hunter, 1929, based on specimens from the type host, small mouth buffalo, Ictiobus bubalus . This cestode is mainly typified by an elongate bottle-shaped body with a narrow, long neck region distinctly separating a relatively large scolex with deep loculi and a sharply widening body. Molecular phylogenetic analysis based on sequences of the large subunits of the nuclear ribosomal RNA genes ( lsr DNA or 28S rDNA) placed B. giganteum in a clade called herein the B. giganteum -species complex, which also includes two morphologically similar new species. Biacetabulum magdae sp. nov. is described from the blacktail redhorse, Moxostoma poecilurum (type host), and the spotted sucker, Minytrema melanops, in Mississippi, USA. It differs from B. giganteum by the scolex with a weakly developed apical disc and shallow median and lateral loculi. Biacetabulum johni sp. nov. is described from Minytrema melanops (type host) in Florida and Moxostoma poecilurum in Mississippi, USA. Biacetabulum johni sp. nov. can be distinguished from B. magdae sp. nov. by a smaller size of the body (5–7 mm versus 10–12 mm) and a relatively longer neck, with the first vitelline follicles beginning at about the mid-length of the body in B. johni (versus at the first third or fourth of the body in B. magdae ). With two new species described herein, Biacetabulum becomes the most species-rich genus of caryophyllidean tapeworms, with a total of 14 nominal species known to date (recently described B. hypentelii is synonymized with B. longicollum based on newly generated molecular data). Host specificity of species of Biacetabulum Hunter, 1927 was critically reviewed and it is shown that the actual host specificity is considerably higher than that reported in the literature. http://zoobank.org/urn:lsid:zoobank.org:pub:lsid:zoobank.org:pub:ABF5446A-F170-4CA0-9AF7-D5234BD71139